Pervasive prejudice?: unconventional evidence of race and gender discrimination - Ayres, Ian (Studies in law and economics)
Machine generated contents note: Part I Disparate Treatment -- 2 Gender and Race Discrimination in Retail Car -- Negotiations (with Peter Siegelman) -- 3 Toward Causal Explanation -- 4 Discrimination in Consummated Transactions -- 5 Legal Implications -- Part II Disparate Impact -- 6 Unequal Racial Access to Kidney Transplantation -- (with Laura G. Dooley and Robert S. Gaston) -- 7 A Market Test for Race Discrimination in Bail -- Setting (with Joel Waldfogel) -- Part III Affirmative Action -- 8 How Affirmative Action at the FCC Auctions -- Decreased the Deficit (with Peter Cramton) -- 9 Expanding the Domain of Civil Rights -- Empiricism